How community initiatives are making a difference in goat farmers’ lives in Central Mozambique - Homann-Kee Tui, Sabine; Sixpence, C.; Quembo, C. (2019)
In risk prone farming areas like Marara District, goats are a profitable and resilient source of income. A goat restocking and pass-on approach – providing goats to extremely poor farmers who would then pass on the goats’ first offspring to other farmers – was developed, thus enabling the farmers to participate in local development pathways via goat farming. Benefits were identified at different levels of participation. Selling goats enables smallholder farmers with the means to pay for food, education, human health and farm labor, enabling them to transition to a better livelihood. For communities, an activity such as restocking strengthens their capacity to respond to threats (drought, theft) by building a common knowledge base and developing assets. Stakeholder networks bring goat market partners closer for cost-effective collection and sale/purchase of goats